Urban morphology and disaster risk reduction: A systematic literature review - Qinglong An; Chiho Ochiai (Progress in Disaster Science)
Frequent climate change increasingly exposes cities to multi-disaster risks, directly threatening human safety and well-being. Urban morphology shares theoretical content and spatiotemporal characteristics with Disaster Risk Reduction (DRR). Exploring the relationship between urban form and disaster risk is particularly important to guide urban design and policymaking. To understand how urban form contributes to DRR, this study employed bibliometric and content analyses to review relevant literature based on a theoretical study rooted in urban morphology and DRR. Specifically, this review examined existing research trends, and the methods, data, and key elements of urban form utilized at different scales. The result reveals the progress in urban morphology and DRR research, which is driven by global frameworks such as the Yokohama Strategy, Hyogo Framework for Action, and Sendai Framework for Disaster Risk Reduction. Key gaps include spatiotemporal complexities, precise disaster risk data, and sociocultural factors. Quantitative methods dominate current research, but the integration of qualitative methods including transect walks, stakeholder interviews and cultural mapping provides complementary insights into the socio-cultural dimensions behind urban form, and implicit disaster response mechanisms in urban resilience. Future research should broaden cross-regional studies, incorporate multi-hazard perspectives, and integrate disaster cycles to develop more comprehensive and globally applicable policies.